Students Creativity in Extracurricular Activities at Indonesian Natural School - Sepvia, Sinta; Husin, Azizah; Ratna Kartikawaty, Evy (Universitas Negeri Semarang, 2022)
Changes in contemporary life, such as concerns about lack of physical exercise, poor mental health, and the problems of climate change and environmental degradation, it can be argued that there is a greater need for children to be in touch with nature, for children to be interested in the environment. This study aims to describe the implementation of extracurricular craft and extracurricular comic activities and measure the creativity of these students as a result of the learning process in extracurricular activities at Sekolah Alam Indonesia in Palembang City. This research is qualitative descriptive research and supported by quantitative data. Data collection techniques use structured interviews, then corroborated with observation techniques, and documentation. Measurement of participants' creativity was carried out through descriptive statistical analysis with scoring and categorization. The results showed that in the learning process of extracurricular activities, the creativity of craft students tends to develop in the core learning activities compared to comic students. It is concluded that the creativity of students will develop optimally if the learning process is carried out with the right procedures, and the creativity of tutors is needed as a facilitator in conditioning a learning environment that allows students to learn actively and creatively.